(3eOi eSFhdjI GdOhdI Yf CNWGA GdGOGQGJ GdbGfhJjI (B/s - (3aJMi eMeO YHO GdMcje eMeOs; (3QHjY OQOjQ eMeO Ydis; (3hgjH YjGO SdGegs; (3LGeYI CSjhWs (3cdjI GdMbhbs ((3CSjhW(B:s (3cdjI GdMbhb(B-(3LGeYI CSjhW,s, 2011)
(3Ef GdJWhQ GdWHj GdgGFd jaGLF GdYGde cd jhe HGdLOjO aj GdeLGd GdWHj, hCOi Pdc Edi XghQ HYV GdJbfjGJ GdWHjI GdMOjKI, hefgG YedjGJ fbd hRQGYI GdCYVGA HGYJHGQgG CMO GdhSGFd GdYdGLjI GdegeI hGdVQhQjI aj YdGL HYV GdMGdGJ GdeQVjI, hcPdc ENVGY LSe GdEfSGf ddJLGQH GdWHjI hJWHjbGJgG GdeNJdaI eKd GdgfOSI GdhQGKjI hGdGSJfSGN hGdYdGL HGdNdGjG GdLPYjI HeG JMedg ef BeGd hCMdGe ddeQVi ef CLd GdbVGA Ydi BdGege GdeNJdaI(B. (3hcd gPG jfWhj Ydi eSGS HLSe GdEfSGf GdPj jNVY deHOC eYUhejI GdLSO, hdPdc cGf ef GdVQhQj GdHMK Yf eOi eTQhYjI JWHjb gPg GdJbfjGJ Ydi LSe GdEfSGf ef NdGd OQGSI eOi eTQhYjI GdJUQa aj GdCYVGA GdBOejI aj GdTQjYI hGdbGfhf, hgh eG MGhdfG GdhUhd Edjg aj gPG GdHMKs
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI CSjhW, cdjI GdMbhb, bSe GdbGfhf GdYGe (B2011s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: (3UaMI (B888-942s
Keywords: (3GdTQjYI GdGSdGejIs; (3eSFhdjg GdOhdgs; (3GdeSFhdjI GdGOGQjIs; (3hdGjI GdMSHIs; (3OjhGf GdeXGdes; (3GdNWC GdeQabjs; (3hdGjI GdeXGdes; (3GdeTQhY GdYGes -- (3LGeYI CSjhWs -- (3GdbGfhf GdYGes